Use of a modified Delphi approach to develop research priorities for the Association of Coloproctology of Great Britain and Ireland. (December 2014) - Tiernan, J.; Cook, A.; Geh, I.; George, B.; Magill, L.; Northover, J.; Verjee, A.; Wheeler, J.; Fearnhead, N.
Abstract Aim The modified Delphi approach is an established method for reaching a consensus opinion among a group of experts in a particular field. We have used this technique to survey the entire membership of the Association of Coloproctology of Great Britain and Ireland (ACPGBI) to reach a consensus on prioritizing clinical research questions in colorectal disease. Method Three rounds of surveys were conducted using a web‐based tool. In the first, the ACPGBI membership was invited to submit research questions. In Rounds 2 and 3 they were asked to score questions on priority. A steering group analysed the results of each round to identify those questions ranked as being of highest priority. Results Five hundred and two questions were submitted in Round 1. Following two rounds of voting and analysis, a list of 25 priority questions was produced, including 15 cancer‐related and 10 noncancer‐related questions. Conclusion It is anticipated that these results will: (i) set the research agenda over the next few years for the study of colorectal disease in the United Kingdom, (ii) promote development and (iii) define funding of new research and prioritize areas of unmet clinical need where the potential clinical impact is greatest.